The long-term observation of the rotation of implantable collamer lens as the management of high postoperative vault - Jiang, Yang; Luo, Yan; Li, Ying; Lu, Thomas (Frontiers in Medicine, 2023)
Purpose: To describe the effectiveness and stability of implantable collamer lens (ICL) rotation in reducing high postoperative vault. Setting: Peking Union Medical College Hospital, Chinese Academy of Medical Sciences Design: Retrospective case-series Methods: Twenty-two eyes from twenty-two patients who had ICL (V4c EVO+) implantation with high postoperative vault(>=750um) were recruited for our study. All the lens were rotated from horizontal to oblique position. The vault, SSA, AOD500, AOD750, TISA500 and TISA750 at 180°and 0°were measured pre-rotation, 1 week post-rotation and in the at least 1year follow-up. Results: Twenty females and two males were recruited, with the mean age of 28.68±6.08y. The mean vault had declined significantly from 951.81±154.26 µm pre-rotation to 772.27±119.40 µm 1 week post-rotation (p < 0.001). The SSA, AOD500, AOD750, TISA500 and TISA750 at 180°and 0°pre-rotation and 1 week post-rotation were 30.40±7.91° and 45.14±6.75°, 32.37±7.48° and 46.23±6.39°, 303.27±87.99 and 522.45±122.16um, 323.81±89.15 and 536.13±121.66um, 387.95±99.43 and 630.81±133.59um, 435.68±106.72 and 643.36±132.82um, 0.109±0.034 and 0.202±0.053mm2 , 0.123±0.034 and 0.212±0.051mm2，0.194±0.056 and 0.345±0.083mm2，0.216±0.055 and 0.358±0.079mm2 (all p < 0.001) .The mean vault value had changed from 747.50±116.07um 1 week post-rotation to 586.87±132.65um in the at least 1year follow-up. However, the SSA, AOD500, AOD750, TISA500 and TISA750 at 180°and 0°had remained stable (p>0.05). Conclusion: Non-toric ICL rotation is a novel and effective technique in the treatment of high postoperative vault. Our results are more robust given the extended period of follow-up.